IL33: Roles in Allergic Inflammation and Therapeutic Perspectives - Chan, Ben C. L.; Lam, Christopher W. K.; Tam, Lai-Shan; Wong, Chun K. (Frontiers in Immunology, 2019)
Interleukin (IL)-33 is a member of the IL-1 cytokine family constitutively expressed in structural and lining cells including fibroblasts, endothelial cells and epithelial cells of skin, gastrointestinal tract and lungs that are exposed to the environment. Different from most cytokines that are actively secreted from cells, nuclear cytokine IL-33 is released passively during cell necrosis or when tissues are damaged, suggesting that it may function as an alarmin that alerts the immune system after endothelial or epithelial cell damage during trauma, physical stress or infection. IL-33 plays important roles in type-2 innate immunity via activation of allergic inflammation-related eosinophils, basophils, mast cells and group 2 innate lymphoid cells (ILC2s) through its receptor ST2. In this review, we focus on the recent advances of the underlying intercellular and intracellular mechanisms by which IL-33 can regulate the allergic inflammation in various allergic diseases including allergic asthma and atopic dermatitis. The future pharmacological strategy and the application of traditional Chinese medicines targeting the IL-33/ST2 axis for anti-inflammatory therapy of allergic diseases will also be discussed.